METHODOLOGICAL ISSUES OF ECONOMIC ANALYSIS AT VARIOUS STAGES OF JURIDICAL PERSONS’ REORGANIZATION - O. S. Bezvidnaya (Russian Journal of Economics and Law, 2013)
Objective: to define the methodological features of economic analysis at various stages of juridical persons’ reorganization. Method: abstract-logical. Results: the main stages of juridical persons’ reorganization are defined; preliminary, preparational, registration, concluding. The main directions of economic analysis are defined and grounded for each reorganization stage, as well as its aims, objectives, informational basis and methodological issues. Scientific novelty: the main stages of juridical persons’ reorganization are defined, which are connected with certial managerial decisions and controlling-analytical work. The main features of analytical work are defined for various stages of reorganization. Practical value: possibility to choose the optimal managerial decisions resulting from analytical work when making decisions on reorganization, its optimal forms and during its implementation.